Optimizing restricted feeding strategies to improve tilapia (Oreochromis niloticus) growth and feed utilization - Aries, Gusti; Khairat, Miftahul; Rahardjo, Sinung; Sari, Yesi Dewita (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Excessive feeding not only increases production costs, but also it can pollute the environment due to unconsumed feed residue. One of the strategies that can be used to increase aquaculture efficiency is by implementing restricted feeding techniques. This study aimed to evaluate the impact of different restricted feeding intervals on tilapia growth performance, feed conversion ratio (FCR), survival rate (SR), and feed cost efficiency. This study used a Completely Randomized Design (CRD). The study consisted of three treatments and four replications using one container separated using net partition in a pond with a rearing period of 50 days. Periodic restricted feeding affected the growth of tilapia length and weight, but did not affect Survival Rate (SR) and Feed Conversion Ratio (FCR). The highest rate of growth was shown by P2 (restricted feeding period of 1 day) with a length of 8.79 3.18 cm and a weight of 9.46 3.18 g, and the lowest rate of growth was in treatment P3 (restricted fasting period of 2 days) with a length of 8.2 1.82 cm and a weight of 7.47 2.45 g. Although FCR and SR did not differ significantly across treatments, P2 had the lowest FCR (0.76) and highest SR (83%), with a 23% reduction in feed cost compared to P1. In conclusion, restricted feeding with one fasting day per week improved tilapia growth and feed utilization efficiency, offering a cost-effective and sustainable feeding strategy for aquaculture.Keywords:TilapiaGrowthFeed conversion ratioSurvival rateCompletely randomized design